2016
DOI: 10.1002/adv.21569
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cross‐linked Superfine Alginate‐Based Nanofibers: Fabrication, Characterization, and Their Use in the Adsorption of Cationic and Anionic Dyes

Abstract: In this study, fabrication, characterization, and adsorption properties of alginate (Alg)-based nanofibrous membrane were investigated for two categories of anionic (AR14) and cationic (BB41) dyes. Three optimization steps were performed to achieve the membrane enjoying desirable morphology, highest Alg content, and lowest possible nanofiber diameter. Consequently, Alg/poly(ethylene oxide) nanofibers with the 80:20 ratio and mean diameter of 93 nm were produced. A novel method was applied as spraying the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Poly(aspartic acid) 7.4 [87] Swelling [88] Poly(boronic acid)s Poly (3-acrylamidophenyl boronic acid) (PABA) 8.0 [89] Swelling [2] Polybasic Natural polymers Chitosan 6.1 [90] Swelling Degradation [91][92][93] Alginic acid 3.5 [94] Swelling Solubility [95] Amino-based Polymers Poly((2-dimethylamino) ethylmethacrilate) (PDMAEMA) 7.5 [96] Swelling [97] Pyridine-based polymers Poly(4-vinylpyridine) (P4VP) $3.2 [98] Swelling Wettability [99,100] Copolymers Poly(styrene-co-maleic sodium anhydride) [101] Swelling [102] Chitosan-g-poly(N-isopropylacrylamide)…”
Section: Poly(carboxylic Acids)mentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(aspartic acid) 7.4 [87] Swelling [88] Poly(boronic acid)s Poly (3-acrylamidophenyl boronic acid) (PABA) 8.0 [89] Swelling [2] Polybasic Natural polymers Chitosan 6.1 [90] Swelling Degradation [91][92][93] Alginic acid 3.5 [94] Swelling Solubility [95] Amino-based Polymers Poly((2-dimethylamino) ethylmethacrilate) (PDMAEMA) 7.5 [96] Swelling [97] Pyridine-based polymers Poly(4-vinylpyridine) (P4VP) $3.2 [98] Swelling Wettability [99,100] Copolymers Poly(styrene-co-maleic sodium anhydride) [101] Swelling [102] Chitosan-g-poly(N-isopropylacrylamide)…”
Section: Poly(carboxylic Acids)mentioning
confidence: 99%
“…For example, M. Ghani et al have reported the design of alginate nanofibers for the removal of cationic and anionic dyes. [95] Alginate nanofibers were generated from alginate/PEO (80:20 ratio) mixtures and subsequent crosslinking by carefully spraying a CaCl 2 solution over the fiber membrane. In this way, the PEO dissolved in water, while alginate retained its structure as nanofibers to form a stable membrane.…”
Section: Natural Polymersmentioning
confidence: 99%
“…Swellable electrospun fibers Methylene blue 1834.97 mg g −1 [ 116] Phenolate immobilized fiber Brilliant cresyl blue 890.10 mg g −1 [ 108] PVA/chitosan electrospun nanofibrous membrane Direct red 80 790.00 mg g −1 [ 110] C/NiO-ZnO nanocomposite fibers Congo red 613.00 mg g −1 [ 109] Porous N-carbon/silica nanofibers Methylene blue 397.5 mg g −1 [ 117] Cellulose acetate/poly (dimethyldiallylammonium chloride-acrylamide) nanofibrous membranes Acid black 172 231.00 mg g −1 [ 118] Mesoporous carbon nanofibers Methylene blue 119.21 mg g −1 [ 119] Methyl orange 101.35 mg g −1 [ 119] Poly(methyl methacrylate)/zeolite nanofibrous membranes ZnO nanorods on electrospun fibers Rhodamine B 96.3% [ 107] Methylene blue 92.2% [ 107] Activated carbon fibers-cathodic electro-adsorption Acid orange 7 94.7% [ 111] Alginate (Alg)-based nanofibrous membrane Acid red 14 93.0% [ 128] Basic blue 41 71% [ 128] standard method for the production of nanoscale mats with high surface areas for chemical modification. Superior performance for dye removal has been achieved by modification of natural fibers with amine incorporation, while the presence of functional groups, such as hydroxyl, carboxyl, and carbonyl, in corn fibers and the lignocellulose residue from sugarcane bagasse resulted in outstanding performance for trace metal ion removal.…”
Section: Adsorbentmentioning
confidence: 99%
“…[3,20] The main objectives of RSM are to find the coefficients of a mathematical model to verify the quantitative data obtained from experiments and determine the operational conditions for the system to achieve the optimum response (minimum, maximum, or a targeted value). [21] In this regard, a Box-Behnken design (BBD) was employed to model the electrospinning process and study the effect of three independent parameters on the average nanofibers diameter, namely concentration of the electrospinning solution (X 1 , wt%), applied voltage (X 2 , kV), and the capillary tipcollector distance (X 3 , cm). The experimental range of each parameter, determined based on preliminary visual studies on the stability of electrospinning jet and evaluating the morphology of nanofibers with optical microscopy (OM; Leica-ATC 2000, Germany), is summarized in Table 2.…”
Section: Design Of Experimentsmentioning
confidence: 99%